Combined chromatographic strategy based on macroporous resin, high‐speed counter‐current chromatography and preparative HPLC for systematic separation of seven antioxidants from the fruit of Terminalia billerica. Issue 20 (10th September 2019) - Yang, Xue; Shen, Cheng; Li, Hongmei; Wang, Nana; Ma, Jialin; Wang, Shuo; Zhao, Jingyang; Chen, Jilin; Yang, Li; Chen, Tao; Li, Yulin
Abstract: In the present study, combined chromatographic strategy based on macroporous resin, high‐speed counter‐current chromatography and preparative high‐performance liquid chromatography for systematic separation of antioxidants from crude samples guided by high‐performance liquid chromatography with 1, 1‐diphenyl‐2‐picrylhydrazyl has been successfully established. Based on this strategy, seven antioxidants including isorugosin A, β ‐1, 2, 3, 6‐tetragalloyl‐D ‐glucose, chebulinic acid, 1, 2, 3, 4, 6‐penta‐O‐galloyl‐β ‐D‐glucose, chebulagic acid, ethyl gallate, and gallic acid were obtained from the fruit of Terminalia billerica . First, high‐performance liquid chromatography with 1, 1‐diphenyl‐2‐picrylhydrazyl experiment showed the presence of seven main antioxidants in the crude extract of the fruit of Terminalia billerica . Then, a macroporous resin column chromatography method was developed for the enrichment of these seven antioxidants. Finally, an efficient method based on high‐speed counter‐current chromatography and preparative high‐performance liquid chromatography was developed for the separation of these antioxidants. In the selection of solvent systems, it was found that acetic acid could be a good regulator for modifying the partition coefficient values of tannins. The present study provides a reference for systematic separation of antioxidants from crude samples. Considering the general existence of antioxidants in crude samples, this combined chromatographic strategy might lead to broader application prospects.